Design of POD controller using linear quadratic regulator tecniques for SMIB power system stability enhancement installed with UPFC - Brijesh Kumar Dubey; N. K. Singh (Institute of Advanced Engineering and Science, 2019)
In the field of the power system stability, this paper presents the current research status and developments. This paper presents a systematic approach for designing Power Oscillation Damping Controller (POD) based Linear Quadratic Regulator Techniques for SMIB power system stability installed with UPFC to damp out low frequency oscillations in a power system. The impacts of control strategy on power system single machine infinite bus installed with UPFC, without UPFC and with UPFC and POD controller at different operating conditions are discussed. The accuracy of the developed models is verified through comparing the study results with those obtained from detailed MATLAB programming.